Hepatocellular carcinoma (World Scientific Pub. Co., 2008)
This essential book is a compendium of papers written by an international team of world-renowned experts, who cover topics in their respective areas of expertise. Presenting the most up-to-date knowledge of hepatocellular carcinoma, it covers all topics - including those more controversial ones - in this rapidly advancing field, from epidemiology to prevention, from molecular biology to gross pathology, from screening to atypical presentation, from diagnosis to treatment, and from assessment to choice of appropriate treatment. This volume is therefore an important contribution to the field of hepatocellular carcinoma